Fluctuating Carbonaceous Networks with a Persistent Molecular Shape: A Saddle‐Shaped Geodesic Framework of 1, 3, 5‐Trisubstituted Benzene (Phenine). Issue 28 (6th June 2018) - Ikemoto, Koki; Lin, Jennie; Kobayashi, Ryo; Sato, Sota; Isobe, Hiroyuki
Abstract: A saddle‐shaped macromolecule has been synthesized. The molecule was designed as a geodesic saddle with 1, 3, 5‐trisubstituted benzene (named phenine) as the fundamental unit. The phenines were woven into a polygonal framework that was composed of 168 sp 2 ‐hybridized carbon atoms. The saddle‐shaped structure with unique symmetry showed atypical conformational changes. The biaryl linkages in this molecule had a small energy barrier for rotation, and these structural fluctuations resulted in seven 1 H NMR resonances representing 84 aromatic hydrogen atoms. Nevertheless, the overall saddle shape of the molecule was persistent, and the "up" and "down" orientations of phenine moieties circulated to give average 1 H resonances. The structural characteristics of this molecule, including the anomalous entropy‐driven dimerization, may deepen our understanding of defect‐rich graphitic sheets. Abstract : Stay in the saddle : Planar trigonal 1, 3, 5‐trisubstituted benzene was synthetically woven into an isoreticular geodesic framework corresponding to [7]circulene to form a saddle‐shaped molecule, which revealed a unique fluctuating molecular structure owing to the small energy barrier to rotation of the biaryl linkages (see picture). However, the overall saddle shape of the molecule was persistent.